Incidental Finding of Intrathyroid Metastases of Prostatic Cancer on 18F-Choline PET/CT. (February 2019) - Vija Racaru, Lavinia; Gabiache, Erwan; Fontaine, Sebastien; D'Aure, Dominique; Mourey, Loic; Courbon, Frederic; Zerdoud, Slimane
Abstract : Abstract: An 85-year-old man with a 2-year history of prostate cancer, treated with radiotherapy and hormonal therapy, presented increased prostatic-specific antigen levels. 18 F-choline PET/CT showed focal prostatic uptake consistent with known local recurrence, increased uptake of 2 hypodense thyroid nodules and of 2 left cervical lymph nodes, suspected as thyroid cancer. Neck ultrasound confirmed the high risk of malignancy, and a guided biopsy (of a thyroid nodule and cervical lymph node) revealed cellular infiltrates thyroid transcription factor-1 (TTF-1) negative and prostatic-specific antigen positive, confirming intrathyroid and cervical lymph node metastases of prostate cancer. PET/CT changed the disease staging. Chemotherapy was initiated.